The Harmony of Education and Upbringing in Language Teaching - Mirpayazova Saodat Zafarovna (Scientific Trends, 2024)
This article examines the harmony of education and upbringing in language teaching. The sharp renewal and radical changes that have taken place in our country in recent years require rethinking all spheres of human life from the point of view of globalization and integration processes with new views, concepts and approaches. The future of any country is closely connected with its education in the spirit of future traditions and values. From the last decade of the twentieth century to the present day, as a result of the rapid development of information technology, a sharp increase in the flow of information, both positive and negative situations are increasing.
Keywords: Harmony, education, teaching, upbringing, language, modern youth, views.